Barriers and facilitators of access to HIV prevention, care, and treatment services among people living with HIV in Kerman, Iran: a qualitative study - Zahra Jaafari; Willi McFarland; Sana Eybpoosh; Seyed Vahid Ahmadi Tabatabaei; Mehdi Shafiei Bafti; Ebrahim Ranjbar; Hamid Sharifi (BMC, 2022)
Abstract Background Low access to HIV prevention, care, and treatment services among people living with HIV (PLWH) is a barrier to the control of the epidemic worldwide. The present study aimed to assess the barriers and facilitators to HIV services among PLWH in Kerman, Iran. Methods In this qualitative study, a convenience sample of 25 PLWH who had received HIV prevention, treatment, or care services, and six PLWH who had not yet received services were recruited between August-October 2020. Data were collected using a semi-structured, face-to-face interview. Data were examined by inductive content analysis using MAXQDA 10 software. Results Nine categories of facilitators and 11 categories of barriers to HIV services were identified. Facilitating factors included: maintaining health status, feeling scared, trust in the health system, how they were treated by service providers, provision of suitable hours by the service provider center, changing attitudes towards HIV in society, acceptance of the disease by the patient's family, hope for the future and feeling the need for consulting services. Barriers included financial problems, side effects and belief in efficacy, distance and transportation problems, fear of being recognized, stigma towards PLWH, organization of services, improper treatment by service providers, unsuitable hours by the service provider center, lack of trust in the health system, lack of family support, and inadequate or low-quality service. Conclusion Many facilitators and barriers to HIV prevention, treatment, and care are amenable to change and better management by healthcare and service providers. Addressing these factors is likely to increase the willingness to use services by those who have never previously accessed them.